Splits in students' beliefs about learning classical and quantum physics - Benjamin W. Dreyfus; Jessica R. Hoehn; Andrew Elby; Noah D. Finkelstein; Ayush Gupta (SpringerOpen, 2019)
Abstract Background While there has been increasing recognition of the importance of attending to students' views about what counts as knowing and learning a STEM field, surveys that measure these "epistemological" beliefs are often used in ways that implicitly assume the fields, e.g., "physics," to be a single domain about which students might have sophisticated or naïve beliefs. We demonstrate this is not necessarily the case and argue for attending to possible differences in students' epistemological beliefs across different sub-domains of physics. In modern physics and quantum mechanics courses for engineering and physics students, we administered a set of modified Colorado Learning Attitudes about Science Survey (CLASS) items. Each selected item was turned into two items, with the word "physics" changed to "classical physics" in one and "quantum physics" in the other. Results We found significant splits between students' survey responses about classical vs. quantum physics on some items, both pre- and post-instruction. In classical physics, as compared to quantum physics, students were more likely to report the salience of real-world connections and the possibility of combining mathematical and conceptual reasoning during problem solving. Conclusions These findings suggest that attending to sub-domain specificity of students' beliefs about physics can be fruitful and ought to influence our instructional choices.